Monitoring of basic human vital functions using optical interferometer - Šprager, S; Donlagić, D; Zazula, D (IEEE 10th INTERNATIONAL CONFERENCE ON SIGNAL PROCESSING PROCEEDINGS, 2010)
In this paper, a method is presented for monitoring of basic human vital functions (heartbeat and respiration) by using optical fibre interferometer. Optical fibre interferometer is a sensitive device which detects physical changes of the optical fibre length. If a person is in physical contact with the fibre, such as having it in bed, the fibre interferometers responds to small changes in fibre length induced by the heartbeat and breathing. This allows for unobtrusive and continuous monitoring of a person's vital life signs. The interferometer, however, has a cosine signal transfer characteristic, which complicates the feature extraction algorithms. An experiment was performed with the optical fibre on the mattress. Heartbeat and respiration were extracted using a method based on zero-crossings in the measured interferential signal and a preselected filter bank. The method's recognition rate and accuracy were verified by using reference sensors (an ECG apparatus and nasal air-flow measurements). All signals were acquired simultaneously from 5 male persons in duration of about 60 s. The obtained results prove this simple, unobtrusive approach can monitor human vital signs with fairly high recognition rate: about 95.7% for heartbeat and 93.8% for respiration.